Assessment of the use of fiberglass-reinforced foam concrete in high-speed railway bridge approach involving foundation cost comparison. Issue 2 (January 2020) - Liu, Kai-Wen; Yue, Fei; Su, Qian; Zhou, Chuanbin; Xiong, Zhipeng; He, Yi
In view of the limited use of foam concrete for backfilling high-speed railway bridge approach and no publication considering the associated foundation treatment cost, this article presents a series of laboratory tests to study the mechanical properties of fiberglass-reinforced foam concrete with different contents of fiberglass, whereby the optimal values of target density and fiberglass content for fiberglass-reinforced foam concrete are obtained. A numerical model is developed to investigate the performance of bridge approach filled with fiberglass-reinforced foam concrete under different levels of foundation treatment in comparison with the control group with traditional backfills (combination of graded crushed stone and cement). Results indicate that the application of fiberglass-reinforced foam concrete to fill high-speed railway bridge approach can significantly improve the bridge approach performance (decreasing the horizontal displacement and ground surface settlement, respectively, by 58% and 21% than the control group) and cut down the foundation treatment cost by 19% concurrently.